Investigating the Structural Equation Model of Factors Affecting the Enhancement of Organizational Trust in the Technical and Vocational Organization of Tehran Province - Haddadpour, Samaneh; Nazem, Fattah; Afkaneh, Soghra (Management Strategies and Engineering Sciences, 2025)
This study aims to investigate the factors influencing organizational trust within the Technical and Vocational Organization of Tehran Province. A mixed-methods approach was employed to comprehensively analyze the dynamics of organizational trust. The qualitative phase involved interviews with 10 experts, analyzed using grounded theory to identify key categories and relationships. For the quantitative phase, a sample of 250 employees and managers was selected using stratified random sampling from a population of 2,500. Data were collected using a structured questionnaire with a five-point Likert scale. Structural equation modeling (SEM) was conducted using SmartPLS to evaluate the proposed model's validity and predictive power. Reliability and validity were assessed through Cronbach’s alpha, composite reliability (CR), average variance extracted (AVE), and discriminant validity tests, while structural model fit was confirmed using R² and Q² indices. The results demonstrated that contextual conditions, such as leadership style and organizational culture, significantly influence trust. Intervening conditions, including job security and equitable workplace practices, mediated the relationship between organizational strategies and trust. Strategies like empowerment and knowledge-sharing were identified as critical drivers of trust, contributing to positive outcomes such as enhanced employee commitment and reduced turnover intention. The structural model exhibited strong predictive power, with R² values ranging from 0.62 to 0.94 and Q² values exceeding 0.50 for most constructs, confirming its robustness and practical relevance. Organizational trust is a multidimensional construct shaped by leadership practices, cultural factors, and individual perceptions. The findings highlight the importance of transparent communication, equitable policies, and knowledge-sharing initiatives in fostering trust. These insights offer actionable strategies for enhancing trust in organizational settings, contributing to improved employee satisfaction and organizational resilience.